EFEKTIVITAS PENERAPAN BIMBINGAN KELOMPOK DENGAN TEKNIK PSIKODRAMA DALAM MENGURANGI PRILAKU PROKRASTINASI AKADEMIK SISWA KELAS X SMA KP CIKALONGWETAN - Putry Mustika Pratama Soleh; Siti Fatimah; Muhammad Rezza Septian (IKIP Siliwangi, 2026)
This study aims to determine and analyze the effectiveness of the application of group guidance with psychodrama techniques to reduce academic procrastination of class X students, this study was conducted on class X students at SMA KP Cikalongwetan. The data of this study were analyzed using Mixed Methods with Explanatory design. The subjects of this study were class X students of SMA KP Cikalongwetan with a population of 95 students, so the researcher took the number of research samples with a 10% error rate from a population of 95 students, namely 71 students with the number of subjects given intervention being 7 students. This sampling technique was carried out by simple purposive sampling. The results of the study were carried out with statistical analysis using the Statistical Package for the Social Science (SPSS), where the researcher used calculations with validation tests, reliability tests, normality tests, and paired sample t-tests. In the paired sample t-test, the Sig. (2-tailed) value is 0.000 <0.05. It can be concluded that Ho is rejected and Ha is accepted. This shows that group guidance services with psychodrama techniques are effective in reducing academic procrastination in class X students.